2012
DOI: 10.7314/apjcp.2012.13.7.3361
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about Gastric Carcinoma in North of Iran, A High Prevalent Region for Gastric Carcinoma: A Population-Based Telephone Survey

Abstract: Background & Objectives: The most northern and northwestern regions of Iran are at a high risk for gastric cancer. The aim of this study was to assess the general population's awareness about risk factors, symptoms and signs, preventive methods and management of gastric carcinoma in a high prevalence city in the North of Iran. Methods: A cross-sectional population-based telephone survey which was conducted on 3,457 residents of Rasht, the capital city of Guilan Province, to assess their awareness regarding gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…In this study, the knowledge level was relatively lower than those reported in the Korean and Iranian populations,15 16 signifying poor awareness among the Chinese population regarding gastric cancer. Moreover, while participants had relatively good knowledge of lifestyle risk factors, they had a poorer knowledge of disease risk factors.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In this study, the knowledge level was relatively lower than those reported in the Korean and Iranian populations,15 16 signifying poor awareness among the Chinese population regarding gastric cancer. Moreover, while participants had relatively good knowledge of lifestyle risk factors, they had a poorer knowledge of disease risk factors.…”
Section: Discussioncontrasting
confidence: 71%
“…Another reason could be the high media exposure of H. pylori infection: due to the high prevalence of H. pylori infection, several advertisements about H. pylori infection are broadcast in Korea 31. In our study, more than 50% of participants did not identify any warning symptoms of gastric cancer, and this rate was higher than that among Iranians 15. This result shows that poor awareness of warning symptoms is a factor contributing to the high rate of advanced-stage diagnosis of gastric cancer in Chinese patients, and indicates that these warning symptoms could be a good target for awareness-raising initiatives 7…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Iran is a region with a high incidence of stomach cancer especially in Northern parts (Sadjadi et al, 2005;Mansour-Ghanaei et al, 2012). A strong spatial clustering of gastric cancer in both men and women has been described in Mazandaran and Golestan; two provinces of the Caspian Sea shore line (Malekzadeh et al, 2009).…”
mentioning
confidence: 99%
“…Despite a steady decline of its incidence in developed countries, in less developed countries such as those of the Middle and Eastern Asia, South America and Eastern Europe gastric cancer is an important burden on public health (Lee et al, 2013). Most of the northern and northwestern regions of Iran such as Ardabil, Semnan, Golestan, East Azerbaijan, and Tehran are at a high risk of gastric cancer, but the southern provinces show a lower level of incidence (Malekzadeh et al, 2009;Mansour-Ghanaei et al, 2012). It is a multi-factorial disease and develops because of a continuous cell damage caused by life-long exposure to different carcinogens.…”
Section: Introductionmentioning
confidence: 99%